Eating behaviours of normal and overweight female undergraduate students in positive and negative emotions - Sidek, Suriati; Mat Hassan, N. A. A; Hamirudin, Aliza Haslinda; Mohd Abu Bakar, Wan Azdie; Irfan Unal, Tubanur (Rynnye Lyan Resources, 2021)
Emotional well-being affects eating behaviour, whether making an individual eat less or more than they normally do. This paper aimed to compare eating behaviour between normal and overweight female undergraduate students in response to positive and negative emotions. This cross-sectional study was conducted among 166 female university students. Data collection involved the assessments of participants’ anthropometric measurements to obtain body mass index (BMI) and two self-administered questionnaires to measure of eating behaviour in positive and negative emotions; Emotional Appetite Questionnaire (EMAQ) and Eating Junk Food Questionnaire (EJFQ). Data from the two groups were compared to obtain differences in eating behaviour between normal and overweight female undergraduate students in response to positive and negative emotions. Both normal (Mean = 5.96±1.05) and overweight (Mean = 5.60±0.81) participants reported no changes in the levels of eating under positive emotions. The results also showed that both BMI categories “ate less” when they experienced negative emotions. For EJFQ, there was no significant difference in eating junk food between normal and overweight participants in response to positive emotions. However, the results revealed that the overweight group has more tendency to choose pizza (X2(1) = 6.879), p = 0.009) and cake (X2(1) = 7.458, p = 0.006) than the normal group under negative emotions. These results offer an insight that both BMI groups have almost similar eating-related concerns and thus intervention programs can be constructed on distressing eating-related thoughts and emotions among female undergraduate students.